Paul's Letters and their Impact on the Renewal of Christianity (Islamic Sciences Journal, 2023)
ABSTRACT                            The call of Christ was based on monotheism, which is the call of all the messengers from Adam to Muhammad (may Allah bless him and grant him peace), but I saw in Christianity after Christ a clear deviation from this belief that was preached by Moses, peace be upon him, and after him Jesus, peace be upon him. It is clear that monotheism has disappeared in the beliefs that Christians believed in after that. Paul (the saint of the Christians) is considered the founder of Christianity based on the doctrine of the Trinity (multiple gods). The divinity of the Holy Spirit was also established in this council, just as the divinity of Christ was established in the Council of Nicaea. Then they believe that the second hypostasis of Allah, that is, the hypostasis of the Son, is the one who incarnated and became a real human being. Paul was a Jew of origin, born in Tarsus, in Cilicia, in Asia Minor.